Danish translation and validation of the Self-reported foot and ankle score (SEFAS) in patients with ankle related fractures. Issue 5 (July 2021) - Erichsen, J.L.; Jensen, C.; Larsen, M.S.; Damborg, F.; Viberg, B.
Highlights: Danish language version of the self-reported foot and ankle score (SEFAS) satisfactory evaluate physical function in patients with ankle related fractures. Danish language version of the SEFAS shows good psychometric properties and proofed to be a reliable and valid PROM. Danish language version of the SEFAS satisfactory evaluate physical function in patients with ankle related fractures. Abstract: Background: The Self-reported Foot and Ankle Score (SEFAS) is a patient-reported outcome measure used to evaluate foot and ankle disorders. The purpose of this study was to translate, cross-culturally adapt and validate the Danish language version of the SEFAS in patients with ankle-related fractures. Methods: Forward–backward translation, cross-cultural adaption and validation were performed. In total, 125 patients completed the SEFAS-DK and the Danish version of American Orthopaedic Foot and Ankle Score (AOFAS-DK) at three time points after the date of fracture. The evaluation was performed according to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines. Results: The intra-class correlation coefficient (ICC) level of the SEFAS-DK total score was 0.93 (95% confidence interval [CI]: 0.88–0.96). Cronbach's alpha (CA) for the SEFAS-DK was 0.93, while the floor and ceiling effect at week 6 post-injury was 22.4%. Construct validity was correlated with the AOFAS, and >75% of the pre-defined hypotheses could be confirmed. Responsiveness was analysed using longitudinal data. The minimal clinical important change (MCIC) showed that the SEFAS-DK detects changes in physical function over time. Conclusion: The Danish version of the SEFAS showed overall good reliability, validity and responsiveness. SEFAS-DK can be used to evaluate physical function in patients with ankle-related fractures. Level of evidence: level II, prospective cohort study.